Physicochemical, colour, textural, rheological and sensory properties of goat milk mozzarella cheeses as affected for acidulants: Goat milk mozzarella cheese with acidulants.. - Verma, Arun; Singh, Tarun Pal; V., Rajkumar; K., Gururaj; Singh, Manoj Kumar; Kushwah, Tanuja (Indian Journal of Dairy Science, 2023)
The present study aimed at investigating the effect of four acidulants, viz., acetic acid (CAA), citric acid (CCA), hydrochloric acid (CHA) and lactic acid (CLA) quality and acceptability of goat milk mozzarella cheese. No significant differences in the values of cheese yield, pH, protein and fat were observed among treatments. However, titratable acidity for CCA was significantly higher (p